A life cycle approach to solvent design: challenges and opportunities for ionic liquids – application to CO2 capture. Issue 2 (22nd December 2020) - Cuéllar-Franca, Rosa M.; García-Gutiérrez, Pelayo; Hallett, Jason P.; Mac Dowell, Niall
Abstract : CO2 capture and storage is widely anticipated to play a key role in combatting climate change, however the solvents proposed for use have embedded environmental concerns. Abstract : CO2 capture and storage is widely anticipated to play a key role in combatting climate change, however the solvents proposed for use have embedded environmental concerns. This has led to efforts to develop so-called "green solvents" such as ionic liquids. However, this "green" assertion does not account for the production and disposal phases of solvent life, nor take into account other factors, apart from their "task", that will have an impact on their overall environmental sustainability. The absence of a "cradle-to-grave" evaluation introduces a risk burden shift, thus, this paper presents a life cycle approach to identify the main hotspots across the application of an ionic liquid to a post-combustion CO2 capture process. With a focus on the solvent, molecular-level weaknesses in the design and synthesis, and potential opportunities for improvement are identified. We contrast the use of 1-butyl-3-methylimidazolium acetate or [Bmim][OAc] with a 30 wt% MEA solvent, using an unabated power plant as a baseline. Using MWhe as the functional unit, we observed that the IL-based process reduces the global warming potential of electricity generation by 50% relative to the unabated plant, however this outcome is 43% higher than the conventional amine process. In fact, the so-called "green solvent" actually represented the worst option when considering the full spectrum of environmental impacts. The general incorporation of this approach in solvent development will be vital to ensure genuine progress in tackling climate change, and not simply shifting the burden to other areas.